2021
DOI: 10.1186/s12885-021-08549-2
|View full text |Cite
|
Sign up to set email alerts
|

Modified FOLFIRINOX versus gemcitabine plus oxaliplatin as first-line chemotherapy for patients with locally advanced or metastatic cholangiocarcinoma: a retrospective comparative study

Abstract: Background Gemcitabine plus platinum as the first-line chemotherapy for cholangiocarcinoma (CCA) has limited efficacy. The aim of this study was to evaluate the effectiveness of modified FOLFIRINOX (mFOLFIRINOX) compared to that of gemcitabine plus oxaliplatin (Gemox) for patients with locally advanced or metastatic CCA. Methods From January 2016 to December 2019, consecutive patients who were diagnosed with locally advanced or metastatic CCA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Since FOLFIRINOX signi cantly improved the survival in patients with metastatic pancreatic cancer [26], it had been recognized as an attractive regimen worthy of evaluation in BTC. Actually, as shown in Table 5, several retrospective studies reported the promising activity and tolerability of FOLFIRINOX both as rstand second-line treatment, with a median PFS of 5.0-9.9 months, OS of 9.5-15.7 months and an ORR of 16.0%-33.3% [20][21][22]24]. Favorable results were also observed in a prospective study focused on gallbladder cancer which generally harbors worse survival compared with other BTC; a median PFS of 8.3 months, OS of 10.2 months and an ORR of 48.2% [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since FOLFIRINOX signi cantly improved the survival in patients with metastatic pancreatic cancer [26], it had been recognized as an attractive regimen worthy of evaluation in BTC. Actually, as shown in Table 5, several retrospective studies reported the promising activity and tolerability of FOLFIRINOX both as rstand second-line treatment, with a median PFS of 5.0-9.9 months, OS of 9.5-15.7 months and an ORR of 16.0%-33.3% [20][21][22]24]. Favorable results were also observed in a prospective study focused on gallbladder cancer which generally harbors worse survival compared with other BTC; a median PFS of 8.3 months, OS of 10.2 months and an ORR of 48.2% [19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, liposomal irinotecan combined with uorouracil and leucovorin has also been contributed to increase survival in the second-line setting [17]. Furthermore, FOLFIRINOX comprises uorouracil, leucovorin, irinotecan and oxaliplatin has shown activity and tolerability in retrospective and prospective studies for the rst-or second-line treatment of advanced BTC [18][19][20][21][22][23][24]. Therefore, we designed this prospective study to evaluate safety and e cacy of FOLFIRINOX in patients with chemotherapy-naïve, advanced or recurrent BTC.…”
Section: Introductionmentioning
confidence: 99%
“…Since FOLFIRINOX significantly improved the survival in patients with metastatic pancreatic cancer [ 26 ], it had been recognized as an attractive regimen worthy of evaluation in BTC. Actually, as shown in Table 5 , several retrospective studies reported the promising activity and tolerability of FOLFIRINOX both as first- and second-line treatment, with a median PFS of 5.0–9.9 months, OS of 9.5–15.7 months and an ORR of 16.0%-33.3% [ 20 22 , 24 ]. Favorable results were also observed in a prospective study focused on gallbladder cancer which generally harbors worse survival compared with other BTC; a median PFS of 8.3 months, OS of 10.2 months and an ORR of 48.2% [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mFOLFIRINOX regimen included oxaliplatin 65 mg/m 2 , leucovorin 400mg/m 2 , irinotecan 150 mg/m 2 , 5-FU 400 mg/m 2 , and continuous 5-FU 2400 m4 2 (for 46 h), in a 2-week schedule. The dose of the mFOLFIRINOX regimen was modified according to physical condition of the Chinese population and previous regimens used in PC4[ 10 ]. The S-1 monochemotherapy (body surface area [BSA] ≥1.5 m 2 , 120 mg/day; 1.25 m 2 ≤BSA <1.5 m 2 , 100 mg/day; BSA <1.25 m 2 , 80 mg/day, in 2 divided doses for 2 weeks) was administrated every 3 weeks.…”
Section: Methodsmentioning
confidence: 99%